Biological implications of atmospheric and pedospheric levels of heavy metals - Abolanle A A Kayode; Muhammad Akram; Umme Laila; Omar Ali Al-Khashman; Omowumi T. Kayode; Walaa Fikry Mohammed Elbossaty (Advances in Toxicology and Toxic Effects - Peertechz Publications, 2021)
Heavy metals and pollutants are gaining more and more attention nowadays. Heavy metals at high concentrations have an undesirable effect on soil, plants, animals, and humans. The high concentrations of these minerals reduce the activity of microbiological organisms, which affect the quality of the soil and is reflected in the inhibition of the physiological activity of plants. If plants absorb these minerals, they affect the food chain and thus reflect on plants and animals. Heavy metals have an effect on water bodies and marine organisms, as water pollution with these minerals leads to an increase in the production of reactive oxygen species that cause harm to fish and marine organisms. Therefore, it is necessary to use fertilizers that are free of those heavy metals in order to get rid of the harmful effects of heavy metals.